2021
DOI: 10.23960/jpp.v11.i1.202104
|View full text |Cite
|
Sign up to set email alerts
|

How Indonesian Primary Teacher Motivate and Trains Critical Thinking Skills during Pandemic?: A Phenomenological Study

Abstract: How Indonesian Primary Teacher Motivate and Trains Critical Thinking Skills during Pandemic?: A Phenomenological Study. Objective: This research aims to describe how teachers motivate and train critical thinking skills during the pandemic. Method: This research was a qualitative study with phenomenological type. The data were collected with a phone-call interview. It was then followed up with a WhatsApp-Group discussion of fifteen primary school teachers at a higher level class in Dawe district, Kudus Municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…The indicators developed in instilling critical thinking skills also vary. A study conducted by Ainun Nikmah et al [2], stated 3 indicators of critical thinking, namely analyzing problems, evaluating, and providing conclusions. From these studies, it can be concluded that critical thinking indicators include formulating problems, answering problems, and evaluating.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The indicators developed in instilling critical thinking skills also vary. A study conducted by Ainun Nikmah et al [2], stated 3 indicators of critical thinking, namely analyzing problems, evaluating, and providing conclusions. From these studies, it can be concluded that critical thinking indicators include formulating problems, answering problems, and evaluating.…”
Section: Resultsmentioning
confidence: 99%
“…In online learning with the PBL method through Zoom meetings, the teacher provides a problem to students that will support critical thinking skills, where students will analyze the problems that are displayed [20]. Teachers can invite students to analyze problems by posting questions, and provide opportunities for students to answer ISSN: 2808-103X Proceedings homepage: https://conferenceproceedings.ump.ac.id/index.php/pssh/issue/view/25 358 (Ainun Nikmah et al [2]. In the study of Prafitasari et al [16], analyzing can be done by identifying the elements of the problem.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations